Effects of speed, agility and quickness training programme on cognitive and physical performance in preadolescent soccer players - Trecroci, A.; Cavaggioni, L.; Rossi, A.; Moriondo, A.; Merati, G.; Norbari, H.; Ardigo,; Ardigò, L. P.; Formenti, D. (PLOS ONE, 2022)
The aim of the present study was to investigate the effect of a short-term (4 weeks) non-soccer-specific training programme based on speed, agility and quickness (SAQ) and a soccer-specific training programme based on small-sided games (SSG) on cognitive and physical performance in preadolescent soccer players. Twenty-one participants were randomly assigned to SAQ group (n = 11) or SSG group (n = 10). They were tested pre and post interventions on physical (5 m sprint, 20 m sprint and sprint with turns of 90°) and cognitive (inhibitory control by means of the Flanker task and perceptual speed by means of the visual search task) performances. Although no significant time x group interactions were observed, the main effect of time was significant for cognitive performance and 5 m and 20 m sprint, showing improvements after both SAQ and SSG. These findings highlight that 4 weeks of SAQ training programme induced comparable improvements in cognitive and physical performance with respect to a soccer-specific training programme based on SSG in preadolescent soccer players. Non-sport-specific activities targeting speed, agility and quickness combined with cognitive engagement (i.e., SAQ) should be useful strategies as soccer-specific activities to be included within a soccer training programme for promoting both physical and cognitive domain in preadolescent individuals.